IgG Anti-ghrelin Immune Complexes Are Increased in Rheumatoid Arthritis Patients Under Biologic Therapy and Are Related to Clinical and Metabolic Markers - Porchas-Quijada, Mildren; Reyes-Castillo, Zyanya; Muñoz-Valle, José Francisco; Durán-Barragán, Sergio; Aguilera-Cervantes, Virginia; López-Espinoza, Antonio; Vázquez-Del Mercado, Mónica; Navarro-Meza, Mónica; López-Uriarte, Patricia (Frontiers in Endocrinology, 2019)
Rheumatoid arthritis (RA) is a systemic autoimmune disease associated with increased risk of cardiovascular disease and metabolic alterations. The mechanisms underlying these alterations remain unclear. Ghrelin is a gastrointestinal hormone with potent effects on food intake, body weight, metabolism and immune response. Recent studies reported the presence of anti-ghrelin autoantibodies in healthy subjects and the levels and affinity of these autoantibodies were altered in anorectic and obese individuals. In this cross-sectional study we analyzed anti-ghrelin autoantibodies in RA patients and evaluated its relationship with clinical, body-composition and metabolic parameters. Clinical measurements of RA patients included the disease activity score-28 (DAS-28), inflammatory biomarkers, autoantibodies (RF and anti-CCP), body composition, glucose and lipid profile. Serum ghrelin levels were measured by enzyme-linked immunosorbent assay (ELISA). Free and total IgG and IgA anti-ghrelin autoantibodies quantification (IgG and IgA isotypes) was performed by in-house ELISA. RA patients had lower IgG anti-ghrelin autoantibodies levels and higher immune complexes percentage (IgG+ghrelin) compared to the control group, while the IgA anti-ghrelin autoantibodies showed no significant differences. In the bivariate analysis, the percentage of IgG anti-ghrelin immune complexes positively correlated with BMI and ghrelin whereas in the multivariate regression model, the variables associated were DAS-28, body weight, visceral fat, LDL-C and TG (R2= 0.72). The percentage of IgA anti-ghrelin immune complexes positively correlated with RF and anti-CCP and the multivariate regression model showed an association with RF and body fat percentage (R2= 0.22).Our study shows an increased percentage of IgG anti-ghrelin immune complexes in RA patients despite ghrelin levels were similar in both groups, suggesting an increase in the affinity of these autoantibodies towards ghrelin. The associations found in the multiple regression analysis for anti-ghrelin immune complexes support the previously reported functions of these natural autoantibodies as carriers and modulators of the stability and physiological effect of the hormone. However, in RA both the disease activity and the RF appear to influence the formation of these anti-ghrelin immune complexes.